Bacterial Consortiums Able to Use Metal-Cyanide Complexes as a Nitrogen Source - María Isabel Igeño; Daniel Macías; María Isabel Guijo; Rubén Sánchez-Clemente; Ana G. Población; Faustino Merchán; Rafael Blasco (Proceedings, 2018)
Most cyanide-containing industrial effluents also contain other cyano-derivatives and high amounts of metals and metal-cyanide compounds. For this reason, the biotreatment of these wastes requires the use of microorganisms capable to degrade all these different cyano-compounds and to tolerate metals. Pseudomonas pseudoalcaligenes CECT 5344 is a cyanotrophic bacterium capable of metabolize cyanide in its free form, but it is not very efficient at degrading metal-cyanide complexes. Therefore, for the optimization of the cyanide biodegradation process it is essential to find and characterize new bacterial strains, capable of assimilating metal cyanide-complexes, to complement the capacities of P. pseudoalcaligenes CECT 5344.